Carcinoma in situ (CIS) of the testis - Ziglioli, F.; Maestroni, U.; Dinale, F.; Ciuffreda, M. (Acta Biomedica Atenei Parmensis, 2011)
Testicular cancer is the most common malignancy in 20- to 34-years-old males. It has been stated that testicular cancer derives from a precocious lesion, the carcinoma in situ of the testis, also known as Intratubular Germ Cell Neoplasia (IGCN) or Testicular Intraepithelial Neoplasia (TIN). This lesion deserves great attention, because the diagnosis of CIS may lead to a precocious diagnosis of testicular cancer. Generally, the diagnosis of CIS is incidental. Every physician should know the management of this precocious lesion, as the correct management of CIS can lead to a decrease of the incidence of overt testicular cancer (the most frequent malignancy in young men). Moreover, the correct diagnosis and management of CIS can shorten the hospital stay, reduce the cost, and improve the social impact of the testicular cancer.